KEMAMPUAN MENULIS PUISI MENGGUNAKAN GAMBAR TOKOH IDOLA SISWA KELAS VII A SMP NEGERI SATU ATAP PETALING TAHUN PELAJARAN 2016/2017 - Rudi Hariyanto; Abdoel Gafar; Firman Tara (Universitas Batanghari, 2018)
This research is intended to describe students ability in wiring poetry by using a picture of their idols in class VII A SMP Negeri Satu Atap Petaling Academic Year 2016/2017. This research uses quantitative descriptive method. The data is taken from students poetry in decribing their idols. This researh uses quantitative analysis. The data analysis is counted by using the percentage of students assessment in writing poetry. The data of the research is 25 students. Based on students result in writing poetry by describing their idols at class VII A SMPN Satu Atap Petaling Academic Year 2016/2017, it can be seen that there are 3 students who got 87,5 who fall into good category; there is 1 student who got 81,25 tat falls into very good category; there are 9 students who got 75 that fall into good category; there are 6 students who got 68,75 hat fall into good categroy; and there are 6 students who got 62,5 that fall into fair category. From those 25 students, the total score is 289 with the total score is 1806,5, and the mean is 72,25 that falls into good category. Hus, students ability in writing poetry in decribing their idols at class students of VII A SMP Negeri Satu Atap Petaling Academic Year 2016/2017 fall into good category.Key Words : ability, writing poetry, picturing idols.